1990
DOI: 10.1113/expphysiol.1990.sp003461
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets in the reflex tachypnoeic response to miliary pulmonary embolism in anaesthetized rabbits

Abstract: SUMMARYExperiments were performed upon twenty-eight male Californian rabbits anaesthetized with sodium pentobarbitone and breathing room air. Successive injections of glass bead emboli (diameter 125,am) caused an increase in respiratory rate, and decreases in tidal volume (tachypnoeic response) and platelet count. The tachypnoeic response was not observed in rabbits that had been rendered thrombocytopaenic by platelet antiserum. Induction of thrombocytopaenia by antiserum was accompanied by tachypnoea which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1990
1990
1997
1997

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Certainly, some metabolites of arachidonic acid (e.g. prostaglandin E2) are capable of evoking a vagally mediated tachypnoeic response, but such responses are not inhibited by MDL 72222 at the concentration used in this study (Armstrong et al 1986).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Certainly, some metabolites of arachidonic acid (e.g. prostaglandin E2) are capable of evoking a vagally mediated tachypnoeic response, but such responses are not inhibited by MDL 72222 at the concentration used in this study (Armstrong et al 1986).…”
Section: Discussionmentioning
confidence: 74%
“…antagonized by pre-treatment with the selective neuronal 5-HT3 receptor antagonist MDL 72222 (Armstrong & Kay, 1985), we have investigated the effect of this compound on the responses evoked by pulmonary embolization. A preliminary account of this work has been presented to the Physiological Society (Armstrong, Kay & Russell, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Since 5-HT is of primary importance in mediating the reflex tachypnoea evoked with the current model of embolism (Armstrong et al 1986), the effect of embolization on the discharge frequency of intrapulmonary C fibres was investigated. The effect of injection of Sephadex G-25 beads (1 mg min-', fifteen injections per animal) was investigated upon four pulmonary C fibres (conduction velocities 1-0-2-0 m s-1).…”
Section: Responses To Embolismmentioning
confidence: 99%
“…We have previously demonstrated that miliary pulmonary embolism, like the administration of intravenous 5-hydroxytryptamine (5-HT), produces vagally mediated tachypnoea which is virtually abolished by pre-treatment with the selective 5-HT3 receptor antagonist MDL 72222 (Armstrong, Kay & Russell, 1986). The vagally mediated tachypnoea could conceivably arise from stimulation of one or more of the three identified intrapulmonary sensory receptors, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The site of action of the 5-HT3 antagonism in the prevention of the systemic effects of 5-HT released in the lung is not centrally located, as MDL-72222 did not interfere with the hypotension induced by cephalic vagal stimulation. Indeed, the presence of 5-HT3 receptors in the so called juxta-pulmonary capillarynerve terminals has been reported (McQueen, 1990) and their stimulation is followed by bradycardia and hypotension in rabbits (Thoren, 1979;Armstrong et al, 1986). Although we cannotexclude arole forplateletactivationoutsidethelunginour experiments it is reasonable to assume that the vast majority of activated platelets are trapped in the pulmonary circulation (Hechtman, 1978).…”
Section: Discussionmentioning
confidence: 99%